2013
DOI: 10.1371/journal.pone.0076784
|View full text |Cite
|
Sign up to set email alerts
|

Recrudescence Mechanisms and Gene Expression Profile of the Reproductive Tracts from Chickens during the Molting Period

Abstract: The reproductive system of chickens undergoes dynamic morphological and functional tissue remodeling during the molting period. The present study identified global gene expression profiles following oviductal tissue regression and regeneration in laying hens in which molting was induced by feeding high levels of zinc in the diet. During the molting and recrudescence processes, progressive morphological and physiological changes included regression and re-growth of reproductive organs and fluctuations in concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 83 publications
(72 reference statements)
3
50
0
Order By: Relevance
“…In accordance with results of the previous study [9], we examined effects of varying concentrations of estrogen in blood on expression of PTGDS during the regression and recrudescence phases of the diet-induced molting period. As illustrated in Fig.…”
Section: Estrogen Regulates Ptgds Expression In the Magnum Of The Ovimentioning
confidence: 75%
See 3 more Smart Citations
“…In accordance with results of the previous study [9], we examined effects of varying concentrations of estrogen in blood on expression of PTGDS during the regression and recrudescence phases of the diet-induced molting period. As illustrated in Fig.…”
Section: Estrogen Regulates Ptgds Expression In the Magnum Of The Ovimentioning
confidence: 75%
“…Gene profiling in the previous study [9] revealed that PTGDS expression decreased 60% in the oviduct at Day 12 as compared with Day 0 whereas it increased 5.6-fold in the oviduct on Day 35 as compared to Day 12 of the period of recrudescence of the oviduct. In accordance with results of the previous study [9], we examined effects of varying concentrations of estrogen in blood on expression of PTGDS during the regression and recrudescence phases of the diet-induced molting period.…”
Section: Estrogen Regulates Ptgds Expression In the Magnum Of The Ovimentioning
confidence: 90%
See 2 more Smart Citations
“…For instance, estrogen stimulates proliferation and differentiation of oviduct cells including tubular glands, goblet cells, and ciliated cells during the period of oviduct development [9][10][11], and estrogens also induce synthesis of egg-white proteins such as ovalbumin, ovomucoid, conalbumin, and lysozyme in the tubular glandular cells of the magnum of the oviduct [12]. In addition, estrogen triggers complete remodeling of the reproductive tract to enhance the subsequent rate of egg production after normal or induced regression and recrudescence phases of the molting period [13]. On the other hand, the laying hen is a well-established animal model for research in epithelial-derived ovarian cancer (EOC) which may arise from genetic mutations and damage of the ovarian surface epithelium of laying hens and women [14,15].…”
Section: Introductionmentioning
confidence: 99%